2020
DOI: 10.31269/triplec.v18i2.1173
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Understanding and Combatting Digital Capitalism

Abstract: This article offers a general description of digital capitalism, understood as a system in which social and economic dynamics revolve around digital corporations and their infrastructures. The aim of this analysis is to help develop strategies to counteract capitalism. It takes an historical perspective, considering capitalism as an evolving system driven by a continuous flight from the law of diminishing returns. Fixed Capital and General Intellect are addressed as key analytical concepts for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The process of realizing the metaverse carried out by Facebook and its allies is actually the implementation of the practice of digital capitalism. Digital capitalism is simply a continuation of capitalism which focuses on its production process on selling digital commodities while maintaining the basic dynamics of capitalism (Rivera, 2020). The practice of digital capitalism is mostly carried out because it does not require the arrangement of many human resources in the organization.…”
Section: Metaverse In Futurementioning
confidence: 99%
See 1 more Smart Citation
“…The process of realizing the metaverse carried out by Facebook and its allies is actually the implementation of the practice of digital capitalism. Digital capitalism is simply a continuation of capitalism which focuses on its production process on selling digital commodities while maintaining the basic dynamics of capitalism (Rivera, 2020). The practice of digital capitalism is mostly carried out because it does not require the arrangement of many human resources in the organization.…”
Section: Metaverse In Futurementioning
confidence: 99%
“…The practice of digital capitalism is mostly carried out because it does not require the arrangement of many human resources in the organization. Digital capitalism only requires the development of knowledge and creativity in assembling innovations (Rivera, 2020). However, digital commodities developed by Facebook, such as advertisements, encourage the practice of digital capitalism to manipulate consumers.…”
Section: Metaverse In Futurementioning
confidence: 99%
“…On the other hand, the development of global-level digital capitalism has generated a series of relevant changes in the educational debate over the last decade (De Rivera, 2020). Some of them respond to the development of the global education industry (GEI; Verger et al, 2016) due to the strengthening of Big Tech companies that have found in education an attractive space for offering their products and expanding their investments.…”
Section: Introduction: Digitalization and The New Governance In Educa...mentioning
confidence: 99%
“…Over the last years, however, a growing number of voices is starting to express concern over the speed at which digitalisation is happening. This critical wave discusses in particular the field of education technologies, with structural critiques such as those of Watters [1], to platforms such as those by Selwyn [2], or more broadly to "digital capitalism" [3]. While these critical voices do exist, they are a minority in a landscape dominated by a general optimism and hype around (education) digitalisation 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing work that addresses the issues discussed so far can range from highly conceptual [5] to quantitative [6] with, however, limited explorations on the intersections between the many disciplines working on this field. Furthermore, relevant initiatives, virtuous examples or experiments such as the LowTechMagazine website 2 [7], CoopCloud 3 , commercial initiatives such as Ungleich's Data Center Light 4 , or the many reflections and examples on the field of "permacomputing" [8] are anecdotally regarded, in institutional discourse, as fringe experiences that cannot be replicated, or applied at scale within institutional boundaries.…”
Section: Introductionmentioning
confidence: 99%